“Between a rock and a hard place”: the “wicked problem” of coproducing chronic oedema care - Dring, Eleanore (2022)
Introduction Coproduction is a term which refers to how customers and service-users contribute to the planning, design, delivery, and implementation of goods and services, with service providers. Contemporary coproduction literature reflects a paternalistic perception of service-users with lower socioeconomic status and their interactions and relationships with specialist and non-specialist health professionals. Background Within the contemporary coproduction literature there is a suggestion that that individuals living within a context of socioeconomic deprivation are less equipped to coproduce care. Whilst service-users living with LTCs may have the knowledge, skills to manage their LTC despite socioeconomic disadvantage, there is a lack of research exploring these experiences. This study explored how coproduction is operationalised, and the impact of socioeconomic position and social capital, within the context of ongoing care across hospital and home settings. Theories of coproduction were applied, to explore shared-decision making, the implementation of care “at home”, and the dynamics of power between service-providers and service-users living with long-term conditions (LTC). Methods A mixed methods study was undertaken using, in-depth, face-to-face interviews of service-users from two Lymphoedema Clinics (City and rural) within a regional service; overt non-participant observations within the clinics, to observe the dynamic between the service-users and specialist health professionals. Service-users, partial postcodes and the addresses of General Practitioner” (GPs) were documented to identify the distribution of service-users attending the clinic 1, and to contextualise socioeconomic position of the study setting. NHS ethical approval for the study was obtained through the Regional Ethics Committee, and permission was gained to access all study Sites within the NHS organisations. Findings The findings of this study indicate that socioeconomic status does not prevent service-users from coproducing their care, in terms of their skills and knowledge or the “operant resources” they uses to engage in shared-decision making. However, a lack of economic resources and social capital, or “operand resources”, makes the coproduction of care more challenging for service-users; especially when treatment options are limited, and the implementation of care is within the “home”. In addition, service-users often perceived that non-specialist health professionals lacked the skills, knowledge and expertise to meet their care needs. Care was described by the participants as based upon a traditional, hierarchical and often biomedical model of care. This approach did not always align with the daily life of the participants, which involved balancing condition management against the desire to maintain normality, and achieve the goals that they identified as important The mitigating factor for many of the participants was the social capital and network of support they developed with the SHPs and their significant others; this evolved as an “operand resource”, in terms of trust and reciprocity and the tangible effect of co-implementing and co-delivering care. Conclusion This study addresses the research gaps related to exploration of coproduction for people with LTC, between hospital and home, and the need for more research to empirically evidence service-users’ experience. Social capital, trust, accountability, responsibility, and reciprocity are perceived as essential to operationalise the coproduction of care and actualise a more equitable partnership between service-users and service-providers.